The challenges of Plasmodium vivax human malaria infection models for vaccine development - Roobsoong, Wanlapa; Yadava, Anjali; Draper, Simon J.; Minassian, Angela M.; Sattabongkot, Jetsumon (Frontiers in Immunology, 2023)
Controlled Human Malaria Infection models (CHMI) have been critical to advancing new vaccines for malaria. Stringent and safe preparation of a challenge agent is key to the success of any CHMI. Difficulty producing the Plasmodium vivax parasite in vitro has limited production of qualified parasites for CHMI as well as the functional assays required to screen and down-select candidate vaccines for this globally distributed parasite. This and other challenges to P. vivax CHMI (PvCHMI), including scientific, logistical, and ethical obstacles, are common to P. vivax research conducted in both non-endemic and endemic countries, with additional hurdles unique to each. The challenges of using CHMI for P. vivax vaccine development and evaluation, lessons learned from previous and ongoing clinical trials, and the way forward to effectively perform PvCHMI to support vaccine development, are discussed.